Implementation of The Problem-Based Learning which Combined with Group Investigation in Physics to Improve the Student’s Learning Outcomes - Jusriana, Ana; Wayong, Moh.; Ratnasari, Ita (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2022)
This research is a pre-experimental study which aims to determine the physics learning outcomes of class XI students at public high school 1 Bantaeng using Problem-Based Learning method combined with the Group Investigation Method. We obtained the data through pretest and posttest. The sample in this study was selected using purposive sampling. where the sample consists of one class with 15 people. The results of the descriptive research indicate that there is an increase in student learning outcomes after the method has been implemented. This is proved by the t-test which shows obtained result to be 22,031 where the t table obtained is 1.7613.